Frequent Stock Repurchases, False Signaling, and Corporate Governance: Evidence from Korea. (6th May 2014) - Han, Seung Hun; Lee, Bong‐Soo; Song, Minji
Abstract Manuscript Type Empirical Research Question/Issue We examine the relation between stock repurchases and their potential false signaling of undervaluation using unique Korean data. Research Findings/Insights We find that the firms that repurchase stocks frequently are less undervalued and have lower post‐announcement operating performance than firms that repurchase stocks infrequently. We further find that agency cost and industry‐adjusted Tobin's Q of frequent repurchase firms negatively affect abnormal returns from the repurchase announcement. Corporate governance, especially ownership structure and board independence, affects the probability of frequent signaling. Theoretical/Academic Implications Our results suggest that the main motivation for frequent stock repurchases is likely to be false signaling, and that corporate governance can mitigate false signaling caused by agency cost. Practitioner/Policy Implications Frequent stock repurchases are not necessarily motivated by firm undervaluation. Rather, the degree of agency problems and managers' abuse of information asymmetry tend to increase the frequency of stock repurchases. Therefore, frequent stock repurchases are associated with false signaling by managers; this false signaling can be lowered through better corporate governance. This finding supports the monitoring effect of corporate governance systems.